Polyhedral symmetry from ribbons and tubes. Issue 1 (2nd January 2021) - Boyden, Wilder; Farris, Frank A.
ABSTRACT: A sepak takraw – a ball used for a game in Thailand – is an icosahedrally symmetric shape woven from six bands of rattan. We model it with a multi-parameter family of surfaces, all having icosahedral symmetry. This leads us to ask and answer the question: In how many other ways can we arrange some number of bands in space to create polyhedral symmetry. Our models resemble objects created by other artists; the difference here is that we use Fourier series and focus on the role of the symmetry group. Our general formulas describe a large space of potentially wonderful designs. The instructions always lead to symmetry, but perhaps bad design, until one experiments by altering the parameters. The shapes produced by this method are suitable for artistic development as digital prints or 3D sculptures. We hope that our recipes will empower readers to create their own artistic renditions. GRAPHICAL ABSTRACT: UF0001